HARVESTING COST MODEL FOR SMALL TREES IN NATURAL STANDS IN THE INTERIOR NORTHWEST. - HARTSOUGH, BRUCE R. ; ZHANG, XIAOSHAN ; FIGHT, ROGER D.
REALISTIC LOGGING COST MODELS ARE NEEDED FOR LONG-TERM FOREST MANAGEMENT PLANNING. DATA FROM NUMEROUS PUBLISHED STUDIES WERW COMBINED TO ESTIMATE THE COSTS OF HARVESTING SMALL TREES IN NATURAL STANDS IN THE INTERIOR NORTHWEST OF NORTH AMERICA....